Opinion Leadership Emergence In A Leadership Networked Movement Via Twitter: A Case Study Of #UNDIROSAK - Pauzi, Syibratul Fauzana Mohd (2020)
In recent years, a glaring trend that emerges out of 21st century networked movements — where digital technologies such as social media have a key role in choreographing them — is the rise of leaderless movements. This is where these politically-motivated social movements could run within the absence of any institutional leadership, which raises concerns on the extent of their effectiveness. However, it is found that leaders can still naturally emerge out of these networked movements without any formal appointment or any attempt at a power grab. When trust in representative leadership is decreasing and leaders can emerge naturally out of these leaderless networked movements, it is interesting to understand how they mobilise and sustain. Based on this premise, the researcher attempted to investigate the emergence of leadership within #UndiRosak, a leaderless networked movement where Malaysian voters were weighing the options to spoil their votes in Malaysia’s 14th General Election as a way of expressing dissatisfaction by their limited options of eligible candidates in the election. Guided by three research questions, the study was conducted through a combination of quantitative and qualitative methods, namely thematic analysis and social network analysis, using Twitter data as an archival source. The findings of these research questions suggested that in the absence of traditional institutional leadership in #UndiRosak, a form of opinion leadership — where leaders are identified by their amount of influence within the Twitter network — still emerged.